2019
DOI: 10.1111/dom.13824
|View full text |Cite
|
Sign up to set email alerts
|

Body weight management and safety with efpeglenatide in adults without diabetes: A phase II randomized study

Abstract: AimTo evaluate the safety of efpeglenatide, a long‐acting glucagon‐like peptide‐1 receptor agonist (GLP‐1RA), and its effects on body weight management in adults without diabetes.Materials and methodsIn this phase II, randomized, placebo‐controlled, double‐blind trial, participants with a body mass index (BMI) ≥30 kg/m2 or ≥27 kg/m2 with comorbidity were randomized 1:1:1:1:1 to efpeglenatide (4 mg once weekly, 6 mg once weekly, 6 mg once every 2 wk, or 8 mg once every 2 wk; n = 237) or placebo (n = 60) in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 30 publications
(62 reference statements)
2
43
0
Order By: Relevance
“…Patients receiving semaglutide 2.4 mg in this trial lost 9.9% of their body weight, compared with 0.4% in those receiving placebo [33]. In a phase II study of the longacting GLP-1RA efpeglenatide (4 mg once weekly, 6 mg once weekly, 6 mg once every 2 weeks, and 8 mg once every 2 weeks), patients with obesity and without diabetes had statistically significant reductions in body weight compared with placebo after 20 weeks of treatment (differences in least squares means were -6.3 to -7.2 kg; p \ 0.0001) [36].…”
Section: Clinical Trials Demonstrating Reductions In Body Weight With Glp-1rasmentioning
confidence: 99%
“…Patients receiving semaglutide 2.4 mg in this trial lost 9.9% of their body weight, compared with 0.4% in those receiving placebo [33]. In a phase II study of the longacting GLP-1RA efpeglenatide (4 mg once weekly, 6 mg once weekly, 6 mg once every 2 weeks, and 8 mg once every 2 weeks), patients with obesity and without diabetes had statistically significant reductions in body weight compared with placebo after 20 weeks of treatment (differences in least squares means were -6.3 to -7.2 kg; p \ 0.0001) [36].…”
Section: Clinical Trials Demonstrating Reductions In Body Weight With Glp-1rasmentioning
confidence: 99%
“…The highest placebo-adjusted weight loss was −7.2 kg for a group receiving 6 mg of efpeglenatide once weekly. Gastrointestinal effects were the most common side effects [ 202 ]. Another medication that can be a potential anti-obesity drug is MEDI0382—a GLP-1 and glucagon receptor dual agonist.…”
Section: Incretin Based Therapy For Obesity Treatmentmentioning
confidence: 99%
“…13 14 Efpeglenatide also has unique receptor properties that may explain the greater maximal GLP-1 receptor signaling and reduced desensitization seen with efpeglenatide versus other GLP-1 RAs following chronic exposure in biochemical and preclinical studies. 15 16 Three phase II studies that examined efpeglenatide in both people with T2D 13 14 and people with obesity without T2D 17 found that efpeglenatide was associated with significant decreases in glycated hemoglobin (HbA 1c ) and body weight. With weekly dosing, efpeglenatide was generally well tolerated; the most common AEs were GI disorders, which is consistent with the safety profile of the GLP-1 RA class.…”
Section: Immunology and Transplantationmentioning
confidence: 99%